Primary-Level Government - Zhang, Jing. author. aut Link
XXXII, 330 p.
Keywords: This book examines what constitutes power in rural China, its structure, how it is exercised, and its practical consequences. The author’s explorations are motivated by two key concerns. On one hand, theoretical questions about what rural political reforms in the first half of the 20th century did or did not accomplish continue to demand an adequate answer. On the other hand, any reasonable explanation for the recent surge in social conflicts in rural areas must begin with a sound understanding of how the rural power apparatus shapes both perception and behavior. The ten chapters present in-depth discussions of key issues such as where power comes from, how it is distributed and transmitted, the role of the state, the mechanics of how power is wielded, and what rural social conflicts reveal about both the inertia in politics and where opportunities for change might arise. The author argues that the historical trajectory of change in rural political institutions in the modern era is importantly a legacy of China’s imperial past and more recent traumas. The state-building framework often used to analyze the modernization process in Europe is poorly applicable in the Chinese context, and economic analysis has but limited explanatory power. The book not only contributes to a deeper understanding of contemporary rural politics and governance in China but also sheds light on how the transition from tradition to modernity unfolds within particular historical, sociological and political contexts.